Determinants and Dynamics of Business Aspirations : Evidence from Small-Scale Entrepreneurs in an Emerging Market - Dalton, Patricio S.; Ruschenpohler, Julius; Zia, Bilal (World Bank, Washington, DC, 2018)
Small-scale entrepreneurs are ubiquitous in emerging market economies, yet very few graduate to become larger businesses. This paper asks whether such entrepreneurs aspire to grow and, if so, on which dimensions of the business? What factors influence these aspirations, how realistic are they, and do entrepreneurs dynamically update them based on realized outcomes? A unique panel data set of small-scale retailers in Indonesia is used to show that the average business has strong short- and long-term aspirations for growth in shop size, number of employees, number of customers, and sales. Yet, more than 50 percent of the businesses report no aspirations for growth in the next 12 months, and 16 percent fail to imagine an ideal business over the long term. Entrepreneurs with low profits, business skills, and agency beliefs, as well as those who are older, female, and less educated have significantly lower aspirations. Analysis from a year later shows that most entrepreneurs fail to set realistic aspirations at baseline, but significantly adjust their aspirations to realistic levels with realized outcomes. The analysis also shows that baseline aspirations are a strong predictor of measures of business expansion and innovation, as well as performance outcomes a year later.